Pilates Exercise Impact on Functional Movements, Core Stability and Risk of Injuries in Handball Players - Veronika Šniurevičienė; Laura Baumann; Laura Žlibinaitė (Lithuanian Sports University, 2022)
Background. Handball is a dynamic and physically demanding sport, especially due to the excessive contact of players during the game. The high velocity of the game, high number of matches and the athletic conditioning puts a strain on the musculoskeletal system, leading to a high risk of injury. Prior research substantiates the belief that a better spinal stabilization function due to the application of Pilates exercises would help to achieve better sports results and reduce the risk of injuries. The aim. To evaluate the impact of a Pilates exercise program on functional movements, core stability and risk of injuries in young handball players. Methods. 12 professional handball players aged 18.25 ± 0.45 years participated in the study. A Pilates exercise program was applied in addition to the regular handball training. The program lasted for 8 weeks, with the sessions organized on-line, twice a week for 60 minutes. Before and after the program, functional movements were assessed using the Functional Movement Screen (FMS) method, core stability was assessed by McGill core muscle isometric endurance tests, dynamic stability and associated injury risk was assessed by modified star excursion balance test. Results. After the application of the Pilates exercise program, the evaluation of functional movements according to FMS scores significantly improved (p < 0.05). The isometric endurance ratio of the right and left side core muscles significantly improved (p < 0.05), and the isometric strength endurance ratio between the right side and back muscles also improved (p < 0.05). No significant change in either the total index of dynamic stability of the arms or legs, which indicates the risk of injury was found after the Pilates exercise program. Conclusion. This study illustrates the idea that a Pilates exercise program improved quality of the handball players' functional movements and the isometric strength of some core-stabilizing muscles, while the risk of injuries did not change. Keywords: movement quality, static endurance, dynamic stability, athletes, core stabilization exercise.